(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
At age thirty, I was diagnosed with hereditary rheumatoid arthritis and informed by my rheumatologist that due to the disease, my police and sport careers were over. Thus, began a transition from policing to psychology. I reflect on my journey through the eyes of an existentially oriented psychologist and how these experiences inform my current practice with clients experiencing similar concerns.